Reassessing the non-linear causal link between long-duration commuting and self-rated health: do behavioral preferences and built environment matter? - Qiu, Ning; Li, Wen; Cui, Danrui; Du, Mengbing; Xing, Zibo; Cui, Dongxu; Xinyu, Han (Frontiers in Public Health, 2024)
This study investigates the causal relationship between long-duration commuting and health, assessing how behavioral preferences and built environments influence this dynamic. Utilizing survey data from Jinan, China's most congested city, this study employs Generalized Propensity Score Matching (GPSM) to assess the nonlinear relationships between commuting time and self-rated health. The results indicate that commuting for less than 21 minutes is beneficial to health, the negative effects gradually diminish when exceeding 42 minutes, and are most pronounced at 60 minutes.Heterogeneity analysis shows that women and older adults are more sensitive to long commutes but, together with higher income levels, experience delayed onset of negative effects. Although active commuting generally offers health benefits, it can potentially worsen the commuting-health relationship if extended beyond certain durations. In contrast, regular physical activity continuously enhances a positive influence on this relationship. Moreover, perceived built environment such as residential greenery and walkability contribute to better commuting-health nexus by mitigating the stress associated with commuting. This study deepens our understanding of the non-linear causal relationship between commuting and health, transcending simple correlations to inform targeted interventions that enhance urban health outcomes.